PENGENALAN DUNIA RISET KEPADA KELOMPOK PELAJAR PAPUA DI ARGAPURA RESIMEN GUNUNG KOTA JAYAPURA - Ansanay, Yane Oktovina; Bowaire, Anike Nelce (JURNAL PENGABDIAN PAPUA, 2024)
The community service activity with the title "Introduction to the World of Research to Papuan Student Groups in Argapura Mountain Regiment Jayapura City" was carried out on June 25, 2021, at the Ayalon Argapura Church Building. This service activity focuses on students who are generally at the high school and junior high school level, but in its implementation, there are a number of elementary school students who participated. The service activity was opened by the Head of the Local RT 01/RW 06 and was also attended by a number of church youth. In its implementation, service activities begin with simple questions and answers about knowledge of the world of research, followed by material explanations, simple trial activities and delivery of observations by each group formed. The simple trial activity given is the Water Purification Trial by using materials and tools found in everyday life. It was seen that the participants were very enthusiastic in carrying out test activities and took an active role in providing responses to the observations. Therefore, the activity implementation team concluded that Papuan native students, although initially there was a tendency to be academically inactive, but if they applied the right simple concepts, their thinking and creativity could be developed.